Use of microalgal-enriched Diaphanosoma celebensis Stingelin, 1900 for rearing Litopenaeus vannamei (Boone, 1931) postlarvae - Khatoon, Helena; Banerjee, Sanjoy; Md. Yusoff, Fatimah; Mohamed Din, Mohamed Shariff (Blackwell Publishing, 2013)
The present work investigates the effects of Chaetoceros calcitrans, Nannochloropsis oculata, Tetraselmis tetrahele and Isochrysis galbana diets on the lifespan, growth, neonate production and the nutritional profile of Diaphanosoma celebensis. In addition, the effects of enriched D. celebensis on the survival and growth of Litopenaeus vannamei postlarvae (PLs) was compared with Artemia. Results showed that significantly higher (P < 0.05) neonate production of D. celebensis was attained when fed with C. calcitrans compared to the other microalgae. In addition, D. celebensis fed on C. calcitrans had significantly higher levels (P < 0.05) of protein, lipid and carbohydrate compared to the other three microalgae. On the other hand, D. celebensis had a significantly (P < 0.05) longer lifespan when fed on N. oculata and T. tetrahele compared to those fed with C. calcitrans and I. galbana. Shrimp PLs fed D. celebensis enriched with C. calcitrans had higher survival and specific growth rate but it was not significantly different (P > 0.05) from PL fed only Artemia, indicating that D. celebensis has potential to be used as live feed for the hatchery rearing of L. vannamei PLs, in place of Artemia. This study illustrated that the quality of the D. celebensis production and proximate composition was highly correlated with the food type, and it can be used as a valuable live feed for shrimp larviculture.